2023
DOI: 10.1038/s41396-023-01472-3
|View full text |Cite
|
Sign up to set email alerts
|

Mcr-dependent methanogenesis in Archaeoglobaceae enriched from a terrestrial hot spring

Abstract: The preeminent source of biological methane on Earth is methyl coenzyme M reductase (Mcr)-dependent archaeal methanogenesis. A growing body of evidence suggests a diversity of archaea possess Mcr, although experimental validation of hypothesized methane metabolisms has been missing. Here, we provide evidence of a functional Mcr-based methanogenesis pathway in a novel member of the family Archaeoglobaceae, designated Methanoglobus nevadensis, which we enriched from a terrestrial hot spring on the polysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…M. hypatiae. We hypothesize these subunits are associating together in vivo to bifurcate electrons from hydrogen (H2) to reduce both menaquinone (MQ) and ferredoxin (Fdox), as proposed recently (35,49). Lastly, Ca.…”
Section: Genomic and Transcriptomic Basis For Methanogenesismentioning
confidence: 63%
See 4 more Smart Citations
“…M. hypatiae. We hypothesize these subunits are associating together in vivo to bifurcate electrons from hydrogen (H2) to reduce both menaquinone (MQ) and ferredoxin (Fdox), as proposed recently (35,49). Lastly, Ca.…”
Section: Genomic and Transcriptomic Basis For Methanogenesismentioning
confidence: 63%
“…Collectively, our results and the studies by Wang et al . and Buessecker et al ., who reported that Mcr-encoding Archaeoglobi are present (35) and transcriptionally active in hot spring mesocosms (34), demonstrate the previously overlooked role Archaeoglobi might play in the anaerobic carbon cycle of geothermal environments.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations